Amidine-based ionic liquid analogues with AlCl3: a credible new electrolyte for rechargeable Al batteries. Issue 77 (24th August 2021) - Lucio, Anthony J.; Efimov, Igor; Efimov, Oleg N.; Zaleski, Christopher J.; Viles, Stephen; Ignatiuk, Beata B.; Abbott, Andrew P.; Hillman, A. Robert; Ryder, Karl S.
Abstract : An electrochemical investigation of novel electrolytes based on amidine salts for aluminium batteries. Abstract : Here we demonstrate the generation of novel ionic liquid analogue (ILA) electrolytes for aluminium (Al) electrodeposition that are based on salts of amidine Lewis bases. The electrolytes exhibit reversible voltammetric plating/stripping of Al, good ionic conductivities (10–14 mS cm −1 ), and relatively low viscosities (50–80 cP). The rheological properties are an improvement on analogous amide-based ILAs and make these liquids credible alternatives to ILAs based on urea or acetamide, or conventional chloroaluminate ionic liquids (IL) for Al battery applications.